2001
DOI: 10.1155/s1023621x0100032x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Trapped Vortex Combustor Sector Rig with High‐Speed Diffuser Flow

Abstract: The Trapped Vortex Combustor (TVC) potentially offers numerous operational advantages over current production gas turbine engine combustors. These include lower weight, lower pollutant emissions, effective flame stabilization, high combustion efficiency, excellent high altitude relight capability, and operation in the lean burn or RQL modes of combustion. The present work describes the operational principles of the TVC, and extends diffuser velocities toward choked flow and provides system performance data. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The general description of the combustor and supporting research cell data are similar to those reported in Hendricks et al [4]. The particular aspects of the geometry tested are proprietary and will not be discussed herein.…”
Section: Combustor and Facilitymentioning
confidence: 91%
See 1 more Smart Citation
“…The general description of the combustor and supporting research cell data are similar to those reported in Hendricks et al [4]. The particular aspects of the geometry tested are proprietary and will not be discussed herein.…”
Section: Combustor and Facilitymentioning
confidence: 91%
“…Details of the High Pressure Combustion Research Facility at the Air Force Research Laboratory (AFRL) are provided by Shouse et al [1]. Although some general aspects of the fuel delivery system and operations of the facility are similar to those of [1,4], specific facility modifications and increased capability to handle fuel blending had to be made, including remote alternate test fuel storage/tankage and delivery of the alternate test fuel to the facility fuel pumps, flow meters, and control systems (see Appendix B).…”
Section: Combustor and Facilitymentioning
confidence: 99%
“…And the assumed PDF (probability density function) model was performed to simulate turbulence-chemistry interactions in turbulent reacting flows. The species include C 12 H 23 (fuel), CH 4 The radiation model was the DO (discrete ordinates) radiation model. It can solve exchange of radiation between gas and particulates.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the conventional combustors, TVC employ cavities placed externally [1] or internally [2] as the flame stabilizer. An optimally designed cavity traps a vortex which is spatially and temporally stable over a wide range of inflow conditions [2].…”
Section: Introductionmentioning
confidence: 99%